2019
DOI: 10.1111/bcp.14131
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine may be beneficial in preeclampsia and recurrent miscarriage

Abstract: Recurrent miscarriage (RM) and vasculoplacental disorders, such as preeclampsia (PE), affect women of childbearing age worldwide. Vascular endothelial dysfunction and immunological impairment are associated with both RM and PE. To date, there is no effective or optimal therapeutic approach for these conditions. Notably, aspirin use is only partially effective in the prevention of PE. Hydroxychloroquine (HCQ) has demonstrated beneficial effects on disease flares, pregnancy outcomes and cardiovascular impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 135 publications
3
37
0
1
Order By: Relevance
“…Moreover, the use of HCQ for COVID‐19 is especially not recommended outside of the hospital settings due to the risk of heart rhythm problems. On the contrary, HCQ treatment is needed to control maternal diseases, such as SLE, SS and RA, and decrease the risk of maternal complications such as thrombosis and congenital heart block 34,39–43 . It has also been reported that HCQ may directly be beneficial in obstetric complications such as preeclampsia and recurrent miscarriage 40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the use of HCQ for COVID‐19 is especially not recommended outside of the hospital settings due to the risk of heart rhythm problems. On the contrary, HCQ treatment is needed to control maternal diseases, such as SLE, SS and RA, and decrease the risk of maternal complications such as thrombosis and congenital heart block 34,39–43 . It has also been reported that HCQ may directly be beneficial in obstetric complications such as preeclampsia and recurrent miscarriage 40 .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, HCQ treatment is needed to control maternal diseases, such as SLE, SS and RA, and decrease the risk of maternal complications such as thrombosis and congenital heart block 34,39–43 . It has also been reported that HCQ may directly be beneficial in obstetric complications such as preeclampsia and recurrent miscarriage 40 . Adverse gestational and neonatal outcomes have not been associated with daily maternal doses of HCQ ≤400 mg 21,23,24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antithrombotic action of HCQ [25] may increase placental perfusion and fetal growth. However, HCQ efficacy on very early stages of pregnancy-and possibly in the preconceptional phase-suggests that other mechanisms are involved, including the regulation of complement activity [53], the maintenance of the action of physiological anticoagulants, such as Annexin 5 [29] and modulation of the inflammatory response which is fundamental for successful pregnancy [22]. Further studies are needed to define the mechanisms involved in the protective action of HCQ in pregnant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs compatible with pregnancy in SLE include hydroxychloroquine (HCQ) [20]. HCQ anti-inflammatory effect stems from interference with intracellular Toll-like receptors [21], with phospholipase activity and with the inflammatory cytokines production, thus promoting the TH2 shift typical of a normal pregnancy [22]. Moreover, the agent inhibits platelet aggregation and secretion of arachidonic acid by activated platelets [23,24], decreases the risk of thrombosis and increases overall survival in patients with SLE [25,26].…”
Section: Introductionmentioning
confidence: 99%